The role of surgery in antineutrophil cytoplasmic antibody–associated vasculitides affecting the nose and sinuses: A systematic review. (June 2020) - Pendolino, Alfonso Luca; Unadkat, Samit; Zhang, Henry; Pendolino, Monica; Bianchi, Gerolamo; Randhawa, Premjit S; Andrews, Peter J
Background: The ear, nose and throat region has been reported to be one of the commonest sites involved in antineutrophil cytoplasmic antibody (ANCA)–associated vasculitis diseases and often precedes the diagnosis of ANCA–associated vasculitis by many months. Although treatment for ANCA–associated vasculitis primarily requires systemic immunosuppressive therapy, there are specific indications for sinonasal surgery during the course of the disease process. The three major roles for surgery in sinonasal vasculitis are to aid diagnosis through biopsy, enable symptom relief and nasal reconstructive surgery consideration when in remission. Purpose: The aim of this systematic review is to provide an overview of the surgical procedures which can be performed in patients with ANCA–associated vasculitis presenting with sinonasal involvement. Materials and methods: A systematic literature search was performed for scientific articles on MEDLINE (PubMed Advanced MEDLINE Search) and EMBASE. The search included all articles up to April 2020. Conclusion: Surgical intervention during the active phase of ANCA–associated vasculitis disease can improve the patient's symptoms and enable histological diagnosis. The surgical decision to manage the nose requires a multidisciplinary approach involving the vasculitis specialist and the ear, nose and throat surgeon. Nasal reconstruction can be performed to restore form and function but only when the disease is in remission so as to maximise success and minimise complications.